Estudo epidemiológico das fraturas e lesões do anel pélvico - Pereira, Gilberto José Cação [UNESP]; Damasceno, Erick Ribeiro [UNESP]; Dinhane, Daniel Innocenti [UNESP]; Bueno, Francisco Marques [UNESP]; Leite, Jaqueline Bartelega Rodrigues [UNESP]; Ancheschi, Bruno da Costa [UNESP] (Thieme, 2017)
Objective This study evaluated the pelvic ring fractures and injuries in patients admitted to and treated at this ward between August, 2012 and January, 2014. Methods 66 patients were submitted to treatment protocols according to their age, gender, skin color, injury mechanism, location of the trauma, classification of their injuries, emergency intervention, associated injuries, injured side of the body, treatment, and mortality. The most relevant data were classified according to statistic procedures, such as Goodman's association test. Measures were compared with Student's t‐test and analysis of variance associated with Tukey's multiple comparison test. Results The mean age was 47 years; white race and male gender were most common. Car or truck accident was the most common cause of injuries, which occurred mainly in urban sites. Type A injuries were the most frequent. 16.6% of the cases were submitted to emergency surgery. 42.4% displayed associated injuries. The right side of the body was the most commonly affected side. Non‐invasive treatment was most commonly used. Death was the outcome in 3% of the cases, associated to high‐energy trauma. Conclusions Pelvic ring fractures and injuries are more often verified among males. In general and among younger individuals, traffic accidents are the most common cause of the injury, while among the elderly, ordinary falls are the most commonly verified cause. The majority of those injuries are suffered in urban areas. Type A fractures are more frequent. The majority of cases do not require emergency intervention nor do they feature associated injuries. Non‐invasive treatment is most common and death outcomes are associated to high‐energy traumas with severe injuries.
Epidemiology of pelvic ring fractures and injuries
Keywords: Bone fractures/epidemiology; Epidemiologic studies; Pelvic bones/injuries